Haemopericardium and cardiac tamponade complicating pulmonary lymphangioleiomyomatosis. - Fahy, J (1991)
A case of pulmonary lymphangioleiomyomatosis complicated by haemopericardium and cardiac tamponade is reported. This was successfully managed by creating a subdiaphragmatic extraperitoneal window.